Pengaruh Motivasi Kerja Terhadap Kinerja Guru Di SMP - Lina Luthfiyyah; Didit Darmawan (Universitas Batanghari Jambi, 2026)
Professional educators are a vital component of the education system and a prerequisite for educational institutions. In both formal and informal educational settings, teachers play a central role in teaching and learning activities. Therefore, to achieve better learning outcomes, teachers must consistently improve the quality of their work. The objective of this study is to investigate work motivation and how it influences the performance of junior high school teachers. This study analyzes various academic sources, including reference books, scientific journals, and relevant research articles, using the Systematic Literature Review (SLR) methodology with qualitative descriptive technique The results of this study indicate that work motivation has a positive impact on the performance of junior high school teachers. Work motivation drives productivity, teaching enthusiasm, and teachers readiness to face learning challenges, thereby enhancing teacher performance especially when supported by motivational factors such as the desire to succeed, hard work, and a sense of responsibility. However, this effect is not always consistent, as some studies also indicate that work motivation has a, low orinsignificant impact, likely due to other factors that more strongly influence teacher performance, such as needs, attitudes, and abilities. Thus, work motivation not only encourages educators to improve the quality of their teaching but also fosters a strong sense of discipline and responsibility, both of which directly enhance work productivity and student learning outcomes.